LEGAL ANALYSIS OF THE AUTHORITY OF NATIONAL NARCOTICS AGENCY (BNN) INVESTIGATIONS IN IMPLEMENTING SEARCHES BASED ON THE NARCOTICS LAW AND THE KUHAP - Dwi Frajusi Agustania; Aristoteles; Claudia Yuni Pramita (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Action criminal narcotics is crime outside usual that requires enforcement law effective . Research This aim analyze authority National Narcotics Agency (BNN) investigators in do search based on Constitution Number 35 of 2009 Concerning Narcotics and the Criminal Procedure Code ( KUHAP) as well as implications the law if No in accordance with applicable provisions . Research​ This use method juridical normative with approach legislation . Research results show that Article 75 letter e of the Law Number 35 of 2009 Concerning Narcotics give authority to National Narcotics Agency (BNN) investigators , however in implementation still must comply Article 113 of the Criminal Procedure Code. If action search done without procedure valid law​ so the result can stated No valid and give rise to accountability law , so that required synchronization For ensure certainty law .